Gendhing Pahargyan Temanten at a Traditional Javanese Wedding Ceremony - Hartono, Hartono; Prasetyo, Abdul Rahman (KnE Social Sciences, 2023)
The presentation of music in traditional wedding ceremonies can either be independent (uyon-uyon) or act as an accompaniment. Independent karawitan is served when filling the atmosphere and entertaining guests who are enjoying a meal as well as entertaining them. Marrying with customs is understood as a matter of pride for humans. Among the long traditional processions, one of them is a Javanese traditional wedding ceremony holding great meaning. Marriage is one of many ideals and dreams for a lot of people. Many couples prefer a modern wedding procession because it is more practical, but a few still use customary processions to celebrate it. Despite going through a fairly long and complicated process, the Javanese traditional marriage is still an option for the wider community, especially Javanese people. This Javanese traditional wedding includes a special procedure in the event. Included in the stages of the procession are accompanying music pieces known as gendhing pahargyan temanten. This wedding accompaniment music is believed to have its own meaning by the supporting community. Keywords: gendhing, pahargyan, temanten, ceremony